Odpowiedzialność cywilna ratownika medycznego za błąd medyczny = Civil liability of a paramedic in case of a medical error - Mikos, Marcin; Juszczyk, Grzegorz; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2017)
Mikos Marcin, Juszczyk Grzegorz, Czerw Aleksandra. Odpowiedzialność cywilna ratownika medycznego za błąd medyczny = Civil liability of a paramedic in case of a medical error. Journal of Education, Health and Sport. 2016;6(11):221-224. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166268 http://ojs.ukw.edu.pl/index.php/johs/article/view/3988 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 11.11.2016. Odpowiedzialność cywilna ratownika medycznego za błąd medyczny Civil liability of a paramedic in case of a medical error Marcin Mikos (1), Grzegorz Juszczyk (2), Aleksandra Czerw(2) (1) Polskie Towarzystwo Prawa Medycznego (2) Warszawski Uniwersytet Medyczny, Zakład Zdrowia Publicznego Streszczenie: Ratownik medyczny podobnie jak inni profesjonaliści medyczni może zostać pociągnięty do odpowiedzialności cywilnej za zawinione postępowanie niezgodne ze stanem aktualnej wiedzy medycznej, w wyniku którego pacjent doznał szkody na zdrowiu. Ocena zgodności postępowania ratownika medycznego ze stanem aktualnej wiedzy medycznej jest przedmiotem oceny biegłych sądowych. Za powstałe szkody o charakterze majątkowym i niemajątkowym ratownik medyczny może zostać zobowiązany do wypłaty odszkodowania i zadośćuczynienia. Abstract Paramedics, similar to other medical professionals may a subject of civil liability litigation in case of at fault actions which has been inconsistent with current medical knowledge followed by a loss in health experienced by a patient. The evaluation of accordance of medical activities with current medical knowledge is performed by an expert witness. A paramedic may be obliged to pay a compensation if a financial or nonfinancial loss is proven. Słowa kluczowe: ratownik medyczny, odpowiedzialność prawna, błąd medyczny. Key words: paramedic, legal liablility, medical error.